2021
DOI: 10.1007/s11270-021-05055-w
|View full text |Cite
|
Sign up to set email alerts
|

The Signature of the Coronavirus Lockdown in Air Pollution in Greece

Abstract: The change in atmospheric pollution from a public lockdown in Greece introduced to curb the spread of the COVID-19 is examined based on ground-based and satellite observations. The results showed that in most cases, the change in atmospheric pollution is not statistically significant. It is probably an artifact of the meteorological conditions that contributed significantly to the long-range transport of air pollutants over Greece during the shutdown period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…However, on the contrary, Anand et al (2021a) did not support this idea and directly state this in their paper. In the abstract in the same paper, Zhu et al (2021) concluded: “In recent days, PM exposure could be related as a carrier for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus transmission and Coronavirus disease 2019 (COVID-19) infection.” Ho et al (2021) , citing Setti et al (2020a) : “Second, the SARS-COV-2 virus may spread through the air by attaching to PM2.5/PM10 particles as demonstrated in previous study (35), thereby spreading COVID-19 disease to other people.” Varotsos et al (2021) , citing Setti et al (2020d) : “In addition, the rapid spread of COVID-19 infection in selected areas of northern Italy is believed to be related to PM10 pollution due to airborne particles that may serve as carriers of pathogens ( Setti et al, 2020d ).” Kayalar et al (2021) , citing Setti et al (2020a) : “The only study confirming the presence of virus in atmospheric PM has reported qualitative results (negative or positive) ( Setti et al, 2020b ), . …” …”
Section: Citation Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…However, on the contrary, Anand et al (2021a) did not support this idea and directly state this in their paper. In the abstract in the same paper, Zhu et al (2021) concluded: “In recent days, PM exposure could be related as a carrier for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus transmission and Coronavirus disease 2019 (COVID-19) infection.” Ho et al (2021) , citing Setti et al (2020a) : “Second, the SARS-COV-2 virus may spread through the air by attaching to PM2.5/PM10 particles as demonstrated in previous study (35), thereby spreading COVID-19 disease to other people.” Varotsos et al (2021) , citing Setti et al (2020d) : “In addition, the rapid spread of COVID-19 infection in selected areas of northern Italy is believed to be related to PM10 pollution due to airborne particles that may serve as carriers of pathogens ( Setti et al, 2020d ).” Kayalar et al (2021) , citing Setti et al (2020a) : “The only study confirming the presence of virus in atmospheric PM has reported qualitative results (negative or positive) ( Setti et al, 2020b ), . …” …”
Section: Citation Networkmentioning
confidence: 99%
“… Varotsos et al (2021) , citing Setti et al (2020d) : “In addition, the rapid spread of COVID-19 infection in selected areas of northern Italy is believed to be related to PM10 pollution due to airborne particles that may serve as carriers of pathogens ( Setti et al, 2020d ).”…”
Section: Citation Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many previous studies have pointed out that the intensity drastic variation and fragmentation process of the polar vortex will lead to more extreme weather events, such as cold waves and strong snowfall [5][6][7]. Strengthening of polar vortex intensity will lead to low ozone values, which may have a connection with air pollution and extreme weather events [20,21], further causing sudden changes in the global ecological environment and affecting human health. Among the studies on the effect of polar vortex intensity, Baldwin et al [22] pointed out that the breaking and weakening of the polar vortex are accompanied by the rise of stratospheric temperature and potential height, which affect the global weather change on the surface, and the weak polar vortex event also can cause temperature fluctuations in the lower troposphere and cause the Arctic Oscillation (AO) to have a continuous negative phase [12].…”
Section: Introduction 1concept and Research Backgroundmentioning
confidence: 99%
“…More importantly, severe air pollution episodes occurred during the COVID-19 period in Beijing, with the highest concentration of PM 2.5 reaching 206 µg m −3 . In contrast, the PM 2.5 concentrations have reduced in China and Italy, with no significant change in Greece and most cities in the USA [8][9][10]. This raises interesting questions as to why pollution is increasing in Beijing but not others, and what the major cause of this heavy air pollution in Beijing where the air pollutant emissions experienced a large reduction is.…”
Section: Introductionmentioning
confidence: 99%